Taxonomy of the subgenus Euleptarthrus Jakobson (Coleoptera, Staphylinidae, Osoriinae, Priochirus) of China with descriptions of three new species - Wu, Jie; Zhou, Hong-Zhang (Zootaxa, 2013)
Three new species of subgenus Euleptarthrus Jakobson, 1908 of the genus Priochirus Sharp, 1887 are described from China: P. (E.) trifurcus Wu & Zhou sp. nov. from Xizang, P. (E.) deltodontus Wu & Zhou sp. nov. from Yunnan and P. (E.) curtidentatus Wu & Zhou sp. nov. from Xizang and Yunnan. Diagnoses are also given for two species previously described from China, P. (E.) chinensis Bernhauer, 1933 and P. (E.) subbrevicornis Bernhauer, 1934. An updated version of the key to all Chinese species of the subgenus Euleptarthrus is provided. Important morphological characters are illus-trated.